Sacred, Inviolable, and Unaccountable: The Personal Legal Status of the Emperor of Austria in Constitutionalism - Christoph Schmetterer (Journal on European History of Law)
The document provides an in-depth analysis of the legal status of the Emperor of Austria within constitutionalism, focusing on the concepts of sanctity, inviolability, and irresponsibility ascribed to the monarch in various Austrian constitutional documents and legal frameworks from 1848 to 1867. It explores the historical context, legal interpretations, and implications of these concepts, detailing their impact on the constitutional and legal order of the Austrian Empire. The analysis also delves into the broader implications of the monarch's legal position on the constitutional system and governance.